Exercise for Pregnancy and Pregnant Women Back Pain - Susanti, Neny Yuli; Madhav, Nita (STRADA : Jurnal Ilmiah Kesehatan, 2022)
The main factor that causes lower back pain in pregnancy is the pressure on the back muscles or a shift in the lower spine, which results to joint stress. It can be solved by doing pregnancy exercise carefully for 30 minutes regularly. The objective of the research is to find out the effect of pregnancy exercise in reducing pregnant women’s lower back pain. This pre-experimental research design used pre and post testing for one group subject. The sampling method used in this study was Purposive Sampling. The sample of the research was 14 respondents in Sumberejo Village, Banyuputih Prefecture, Situbondo Region in May. The data was obtained by conducting interview and observation to pregnant women. The data was analyzed by using Wilcoxon Signed Rank Test with the significance rate of ≤0.05. The result of the research showed that most of pregnant women experienced lower back pain, namely 83% respondents.